Using online quizzes for active learning and constructive alignment in a blended learning setting - Udby, Linda (Improving University Science Teaching and Learning, 2023)
In this project on university pedagogics I have experimented with very different types of online quizzes and investigated how they can be used to support different aspects of active and visible learning on a research-based master level course in Physics. The quizzes were not part of the formal assessment of the students but the students were nevertheless very engaged in the quizzes and in most cases felt they achieved deep learning of the topic by working with the quizzes.